Development and implementation of online training modules on abuse, neglect, and exploitation. Issue 2 (27th May 2017) - Ejaz, Farida K.; Rose, Miriam; Anetzberger, Georgia
ABSTRACT: Online training for care managers to identify, report, and prevent abuse, neglect, and exploitation was developed for a demonstration involving the dually eligible Medicare and Medicaid population. It was composed of three modules covering background, screening, and reporting abuse. Of 453 enrollees, 273 completed at least one module and 212 completed all three. Pre- and post-training surveys for each module were used to examine changes in the proportion of correct answers for each question, using the related-samples Cochran's Q statistic. Improvements in knowledge from pre- to post-training were evident in modules covering background on abuse and reporting abuse, but not in the module about communication principles and screening for abuse. Its content may have already been familiar to the trainees, who were primarily social workers and nurses. Lessons learned are being used to adapt the training for a wider audience to increase public awareness of abuse.